2022
DOI: 10.3389/fvets.2022.923238
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic acid: A novel detoxication agent of fumonisin B1 for poultry industry

Abstract: Fumonisin B1 (FB1) is a major fusarium mycotoxin that largely contaminates feedstuffs and foods, posing a health risk to both animals and humans. This mycotoxin can enter the human body directly through contaminated food consumption or indirectly by toxins and their metabolites. In a prior study, feed-borne FB1 is one of the leading mycotoxins in breeder eggs, leading to reduced hatchability and gizzard ulceration in chicken progenies. Currently, no effective way is available to remove FB1 from feeds and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In the present study, a 43.26% detoxifying rate was determined in fresh milk post treatment with 1:2000 concentration of Nb5 concentration. Compared to the anti-FB1 monoclonal antibody, a 25% degradation rate of FB1 was determined post incubation at 25 • C for 2 h in our previous study [25]. Regarding cost-effective detoxification, Nb5 might be a promising detoxifier for combating mycotoxin contamination in the daily milk consumption.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, a 43.26% detoxifying rate was determined in fresh milk post treatment with 1:2000 concentration of Nb5 concentration. Compared to the anti-FB1 monoclonal antibody, a 25% degradation rate of FB1 was determined post incubation at 25 • C for 2 h in our previous study [25]. Regarding cost-effective detoxification, Nb5 might be a promising detoxifier for combating mycotoxin contamination in the daily milk consumption.…”
Section: Discussionmentioning
confidence: 97%
“…Research utilizing piglets challenged with LPS revealed that protocatechuic acid mitigated oxidative stress, inflammation, intestinal barrier impairment, and gut flora disruption (100). Furthermore, protocatechuic acid demonstrates promise as a detoxifying agent against Fumonisin B1 and AFB1 (101,102). Additionally, upregulation of Daidzein, Liquiritigenin, and Naringenin within the OTA-Se group was observed, enhancing Isoflavonoid biosynthesis and Flavonoid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Research utilizing piglets challenged with LPS revealed that protocatechuic acid mitigated oxidative stress, inflammation, intestinal barrier impairment, and gut flora disruption ( 100 ). Furthermore, protocatechuic acid demonstrates promise as a detoxifying agent against Fumonisin B1 and AFB1 ( 101 , 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported severely impaired feed intake and growth of chickens and decrease in feed consumption and average body weight gain up to 12% and 14%, respectively during GEU development (Wang et al 2021). In a recent report, protocatechuic acid (PCA), a naturally occurring phenolic compound, increased the hatchability and decreased GEU of chicks caused by FB1-contaminated corn and feed (Wang et al 2022). Furthermore, PCA exhibited significant antimicrobials against gram-positive and gram-negative bacteria, and fungi.…”
Section: Prevention and Control Strategies Against Geumentioning
confidence: 99%
“…Furthermore, PCA exhibited significant antimicrobials against gram-positive and gram-negative bacteria, and fungi. It also improves humoral and cellular immune responses, suggesting a prospective usage in poultry industry (Guo et al 2018;Wang et al 2022).…”
Section: Prevention and Control Strategies Against Geumentioning
confidence: 99%